Consumer Behavior Practice Oriented Perspectives - Sabah, Senay (IntechOpen, 2017)
No time in the history, consumption is considered to be as important as in today's world. It defines who we are, how well/perfect we perform our multiroles within the society (buying the most expensive clothes means being the best mom for instances), what symbolic meanings we attribute to our belongings, and how rich/clever/fashion conscious or innovative we are. Due to multidisciplinary and multimethod character of the concept of consumer behavior, it is appropriate to study it accordingly in order to understand the subject with its different aspects and holistically. Especially with the cultural, social, and technological changes within today's world, this issue becomes prominent. This book is a modest try for that end.